MOA-2016-BLG-227Lb: a massive planet characterized by combining light-curve analysis and Keck AO imaging - Koshimoto, Naoki; Tsapras, Yiannis (Arxiv, 2017)
We report the discovery of a microlensing planet --- MOA-2016-BLG-227Lb --- with a large planet/host mass ratio of